2018
DOI: 10.1101/255752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allele Phasing Greatly Improves the Phylogenetic Utility of Ultraconserved Elements

Abstract: Abstract.-Advances in high-throughput sequencing techniques now allow relatively easy 20 and affordable sequencing of large portions of the genome, even for non-model organisms. 21Many phylogenetic studies prefer to reduce costs by focusing their sequencing efforts on a 22 selected set of targeted loci, commonly enriched using sequence capture. The advantage of 23 this approach is that it recovers a consistent set of loci, each with high sequencing depth, 24 which leads to more confidence in the assembly of ta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 58 publications
1
69
0
Order By: Relevance
“…The allelic information of the polyploid samples can be condensed to a single consensus sequence to circumvent the challenges of dealing with more than two alleles for phylogenetic approaches. However, the loss of information caused by this simplification might lead to wrong placement of the polyploid accessions in the phylogeny (Eriksson et al 2018; Andermann et al 2019). Our results showed that the thousands of informative sites generated with RAD sequencing contains despite this simplification enough information to resolve the phylogenetic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The allelic information of the polyploid samples can be condensed to a single consensus sequence to circumvent the challenges of dealing with more than two alleles for phylogenetic approaches. However, the loss of information caused by this simplification might lead to wrong placement of the polyploid accessions in the phylogeny (Eriksson et al 2018; Andermann et al 2019). Our results showed that the thousands of informative sites generated with RAD sequencing contains despite this simplification enough information to resolve the phylogenetic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the few model-based programs able to perform this type of analysis. STACEY was demonstrated to outperform the other programs in estimating the correct ultrametric species tree (Andermann & al., 2019), or while inferring the best species delimitation scenario (Tomasello, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Loci obtained by target enrichment are usually longer compared to those from RADseq allowing for gene trees estimation and allele phasing. The importance of the latter has been highlighted in recent studies (Eriksson & al., 2018; Andermann & al., 2019). They demonstrate the advantages derived by retrieving allele information for a correct phylogenetic inference, particularly in recently diverged species complexes where reticulate evolutionary processes play a tremendously important role.…”
Section: Introductionmentioning
confidence: 99%
“…This evolutionary model was chosen using jModelTest version 2.1.4, (Posada 2008) by selecting the model with lowest AIC score and significant likelihood ratio test. In concatenated analyses, choosing one allele at random from heterozygous sites can produce incorrect and biased topologies (Degnan and Rosenberg 2009;Weisrock et al 2012;Lischer et al 2014;Andermann et al 2019). Excluding these sites altogether can bias branch lengths or other parameter estimates (Sota and Vogler 2003;Garrick et al 2010).…”
Section: Lineage Boundaries and Divergence Historymentioning
confidence: 99%